New Achievements in High-Pressure Processing to Preserve Human Milk Bioactivity - Wesolowska, Aleksandra; Sinkiewicz-Darol, Elena; Barbarska, Olga; Strom, Kamila; Rutkowska, Malgorzata; Karzel, Katarzyna; Rosiak, Elzbieta; Oledzka, Gabriela; Orczyk-Pawiłowicz, Magdalena; Rzoska, Sylwester; Borszewska-Kornacka, Maria Katarzyna (Frontiers in Pediatrics, 2018)
High-pressure processing (HPP) is a non-thermal technology that is being increasingly applied in food industries worldwide. It was proposed that this method could be used as an alternative to holder pasteurization (HoP; 62.5oC, 30 min) in milk banks but its impact on the immunologic, enzymatic and hormonal components of human milk has not yet been evaluated in detail. The aim of our study was to compare the effects of HPP in variants : 1) 600 MPa , 10 min 2) 100 MPa, 10 min , interval 10 min., 600 MPa, 10 min 3) 200 MPa, 10 min, interval 10 min., 400 MPa , 10 min 4) 200 MPa, interval 10 min., 600 MPa, 10 min; in temperature range 19 – 21oC and HoP on the leptin, adiponectin, insulin, hepatocyte growth factor (HGF), lactoferrin and IgG contents in human milk. HoP was done at the Regional Human Milk Bank in Warsaw at the Holy Family Hospital on S90 Eco pasteurizer (Sterifeed, Medicare Colgate Ltd). Apparatus U4000/65 (Unipress Equipment, Poland) was used for pascalization. Milk samples were obtained from women during 2-6 weeks of lactation. Post-treatment culture showed no endogenous bacterial contamination in any tested option. Concentrations of selected components were determined using ELISA tests. The level of all analyzed components were significantly decreased by HoP : leptin 77.86,%, adiponectin 32.79%, insulin 32.40%, HGF 88.72%, lactoferrin 60.31.%, IgG 49.04%. All HPP variants caused an increase in leptin concentration, respectively 1) 81.79% 2) 90.01% 3) 86.12% 4) 47.96%. Retention of insulin after HPP was 1) 88.20% 2) 81.98% 3) 94.76% 4) 90.31% HGF 1) 36.15% 2) 38.81% 97.15% 3) 97.15% 4) 43.02%), lactoferrin 1) 55.78% 2) 57.63% 3) 78.77% 4) 64.75%. Moreover, HPP variant as 200 + 400 MPa preserved IgG (82.24%) better than HoP and resulted not statistically significant change of adiponectin level (38.55%) compare to raw milk. Our results showed that HPP leads to preservation of adipokines, growth factor and lactoferrin, IgG much better or comparable with HoP.